On central commutator Galois extensions of rings - George Szeto; Lianyong Xue (International Journal of Mathematics and Mathematical Sciences)
Let B be a ring with 1, G a finite automorphism group of B of order n for some integer n, BG the set of elements in B fixed under each element in G, and Δ=VB(BG) the commutator subring of BG in B. Then the type of central commutator Galois extensions is studied. This type includes the types of Azumaya Galois extensions and Galois H-separable extensions. Several characterizations of a central commutator Galois extension are given. Moreover, it is shown that when G is inner, B is a central commutator Galois extension of BG if and only if B is an H-separable projective group ring BGGf. This generalizes the structure theorem for central Galois algebras with an inner Galois group proved by DeMeyer.